Long term tailored implementation of structured “TREAT” journal clubs in allied health: a hybrid effectiveness-implementation study - Rachel Wenke; Jodie Wiseman; Caitlin Brandenburg; Paulina Stehlik; Ian Hughes; Katherine Richards; Sharon Mickan (BMC Medical Education, 2022)
Abstract Background Allied Health Professionals (AHPs) commonly use journal clubs (JCs) to support Evidence-Based Practice (EBP). There is however little research regarding implementing and sustaining JCs in the long term, and their impact on EBP use and skills in AHPs. This study investigated the impact of implementing a structured JC format, called “TREAT” (previously only investigated across 6 sessions), over a longer period of 16 sessions for AHPs in a public health service. The study also investigated AHP’s attendance, adherence, satisfaction and barriers and enablers to implementing the format. Methods A mixed methods hybrid-effectiveness implementation design was employed, guided by the Knowledge-to-Action cycle. EBP skills, confidence, use, and attitudes were assessed (Adapted Fresno Test, EBPQ, tailored journal club culture questionnaire) at baseline, and after 10 and 16-monthly sessions. Satisfaction and impact on clinical practice were explored using questionnaires at 10 and 16-months, with free-form responses identifying enablers and barriers to EBP culture and implementation. Data on attendance and adherence to the TREAT format were also collected. Results Six JCs comprising a total of 132 unique participants from seven Allied Health professions were assessed across three time points. EBP skills improved on the Adapted Fresno Test after 10-monthly (6.6 points: 95% CI, 0.43 to 12.7) and 16-monthly sessions (7.8 points, 95% CI, 0.85 to 14.7), and on self-reported total EBPQ ratings of confidence at 10-months (4.9 points: 95% CI, 2.2 to 7.5) and 16-months (5.7 points: 95% CI 2.7 to 8.7). Of 132 AHPs, 88 reported adopting new treatments/resources and 64 reported updating clinical procedures. Mean attendance was 5.7 sessions (SD = 3.8). Adherence to TREAT components in each session was 86% (95% CI, 83% to 89%). Most participants recommended the format and reported a desire to continue. Enablers to the JC included using clinically relevant topics and active participation while reported barriers included limited time to prepare. Conclusions Despite variable attendance, TREAT JCs can continue to be implemented within a service for 16 monthly-sessions, and may contribute to improved EBP skills and confidence and changes in clinical practice over time. Tailoring of implementation strategies was shown to be important to address local enablers and barriers.